2023
DOI: 10.1177/17562864231162420
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy and safety of plasmapheresis in elderly patients with neuromyelitis optica spectrum disorder: a single-center observational study

Abstract: Background: Neuromyelitis optica spectrum disorder (NMOSD) is a devastating autoimmune disorder with cycles of escalating relapse. Rates of diagnosis in the elderly are increasing. Therapeutic decision-making is more challenging in elderly patients due to multiple comorbidities and high risk of drug-induced side effects. Objective: This retrospective study assessed the efficacy and safety of standard plasma exchange (PLEX) treatment in an elderly population with NMOSD. Design: Seventy-six patients with NMOSD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Zhang et al concluded in 2023 that PLEX is an effective and safe therapy for elderly patients with NMOSD and should be considered as a treatment option during NMOSD attacks. In the elderly, preventive measures against hypotension are recommended before PLEX [54]. In this study, functional improvement occurred in 88.0% of the elderly patients 1 month after PLEX and increased to 96.0% after 6 months.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Zhang et al concluded in 2023 that PLEX is an effective and safe therapy for elderly patients with NMOSD and should be considered as a treatment option during NMOSD attacks. In the elderly, preventive measures against hypotension are recommended before PLEX [54]. In this study, functional improvement occurred in 88.0% of the elderly patients 1 month after PLEX and increased to 96.0% after 6 months.…”
Section: Discussionmentioning
confidence: 60%
“…Although PLEX is increasingly used in NMOSD-ON, its therapeutic effect and safety are still controversial [53,54]. The fact that PLEX therapy effectively improves visual outcomes was demonstrated in many recent studies [31][32][33]43,54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation